Diagnostic and Prevention Approach in Post Endoscopic Retrograde Cholangiopancreatography Pancreatitis - Stella Ilone; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2016)
Obstructive jaundice (icterus) was an emergency situation in gastroenterology. Endoscopic retrograde cholangiopancreatography (ERCP) was a nonsurgical approach to release obstruction, mostly in common bile duct. Nowadays, this procedure was become frequently used in daily practice, but several complications also emerging. One of the severe complication was Post-ERCP Pancreatitis (PEP). Since it has a high mortality and morbidity, and also reduce patient quality of life, several approaches have been developed to reduce its incidence. In general, approaches consist of patient identification, efficient procedure, until pharmacological agent prevention. Although there were still contradiction among these, careful approach should be considered for each patients for a better outcomes.